When does co-location of manufacturing and R&D matter? - Mikko Ketokivi (The Research Institute of the Finnish Economy (ETLA), 2006)
While both manufacturing and R&D location decisions have received considerable theoretical and empirical attention from economists and organization scientists, theories and evidence regarding the co-location of the two are scarce. The goal of this article is to lay the theoretical foundation for R&D-manufacturing co-location. Theories of functional integration along with qualitative and preliminary quantitative empirical data are used to examine the question: When is co-location of R&D and manufacturing necessary?
Keywords: D21; L23; M11; O32; R32; 330; Location decisions; Co-location; Functional integration; Organization theory; Industrielle Forschung; Verarbeitendes Gewerbe; Betriebliche Standortwahl; Kontingenztheorie